2014
DOI: 10.1002/2014gl061403
|View full text |Cite
|
Sign up to set email alerts
|

First spaceborne observation of the entire concentric airglow structure caused by tropospheric disturbance

Abstract: Spaceborne imagers are able to observe the airglow structures with wide field of views regardless of the tropospheric condition that limits the observational time of the ground‐based imagers. Concentric wave structures of the O2 airglow in 762 nm wavelength were observed over North America on 1 June 2013 from the International Space Station. This was the first observation in which the entire image of the structure was captured from space, and its spatial scale size was determined to be 1200 km radius without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The V-shaped shock wave structure could later evolve to a spectrum of disturbance acoustic waves. Lin The signatures of concentric gravity waves (CGWs) in the middle atmosphere, most commonly triggered by the tropospheric deep convections, are observed using both ground-based and spaceborne airglow sensors [e.g., Suzuki et al, 2007Suzuki et al, , 2013Yue et al, 2009Yue et al, , 2013Vadas et al, 2009;Miller et al, 2015;Akiya et al, 2014]. It is until recently, the CGWs signatures appeared as concentric TIDs (CTIDs) driven by deep convections are observed at the ionospheric height of 250-350 km using Global Navigation Satellite System (GNSS) TEC [Nishioka et al, 2013;Azeem et al, 2015;Chou et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…The V-shaped shock wave structure could later evolve to a spectrum of disturbance acoustic waves. Lin The signatures of concentric gravity waves (CGWs) in the middle atmosphere, most commonly triggered by the tropospheric deep convections, are observed using both ground-based and spaceborne airglow sensors [e.g., Suzuki et al, 2007Suzuki et al, , 2013Yue et al, 2009Yue et al, , 2013Vadas et al, 2009;Miller et al, 2015;Akiya et al, 2014]. It is until recently, the CGWs signatures appeared as concentric TIDs (CTIDs) driven by deep convections are observed at the ionospheric height of 250-350 km using Global Navigation Satellite System (GNSS) TEC [Nishioka et al, 2013;Azeem et al, 2015;Chou et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Concentric wave structures associated with tropical cyclones (TCs) have been detected in mesospheric airglow images (e.g., Suzuki et al 2013;Akiya et al 2014;Yue et al 2014). Typhoon-generated gravity waves have been observed using MU (Middle and Upper atmosphere) radar in the stratosphere (e.g., Sato 1993;Dhaka 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These past studies have revealed the general properties of CGWs, such as launching mechanism and effect of the background wind profile. However, these are mostly single event studies and give only local information [e.g., Taylor and Hapgood , ; Dewan et al ., ; Suzuki et al ., , , Vadas et al ., ; Yue et al ., , ; Akiya et al ., , Azeem et al ., ; Miller et al ., ]. A statistical study on global distribution of the CGWs is needed to gain a more comprehensive understanding.…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, there exists no statistical study of CGWs in the mesopause. Ionosphere, Mesosphere, upper Atmosphere and Plasmasphere/Visible and near-Infrared Spectral Imager (IMAP/VISI) along with Visible Infrared Imaging Radiometer Suite (VIIRS) Day/Night Band (DNB) radiometer on Suomi satellite are among the few space-based instruments that are capable of imaging small-scale gravity waves in airglow emission (several tens of kilometers for IMAP/VISI and~0.74 km for DNB) in the mesosphere and lower thermosphere region [Sakanoi et al, 2011;Akiya et al, 2014;Miller et al, 2015]. Thus, it makes IMAP/VISI suitable for conducting global studies.…”
Section: Introductionmentioning
confidence: 99%